VOx@MoO3 Nanorod Composite for High‐Performance Supercapacitors. (26th July 2018) - Wang, Si‐Qi; Cai, Xiang; Song, Yu; Sun, Xiaoqi; Liu, Xiao‐Xia
Abstract: Vanadium oxide is a promising pseudocapacitive electrode, but their capacitance, especially at high current densities, requires improvement for practical applications. Herein, a VO x @MoO3 composite electrode is constructed through a facile electrochemical method. Fourier transform infrared spectroscopy and X‐ray photoelectron spectroscopy demonstrate a modification on the chemical environment and electronic structure of VO x upon the effective interaction with the thin layer of MoO3 . A careful investigation of the electrochemical impedance spectroscopy data reveals much enhanced power capability of the composite electrode. More charge storage sites will also be created at/near the heterogeneous interface. Due to those synergistic effects, the VO x @MoO3 electrode shows excellent electrochemical performance. It provides a high capacitance of 1980 mF cm −2 at 2 mA cm −2 . Even at the high current density of 100 mA cm −2, it still achieves 1166 mF cm −2 capacitance, which doubles the sum of single electrodes. The MoO3 layer also helps to prevent VO x structure deformation, and 94% capacitance retention over 10 000 cycles is obtained for the composite electrode. This work demonstrates an effective strategy to induce interactions between heterogeneous components and enhance the electrochemical performance, which can also be applied to other pseudocapacitive electrode candidates. Abstract : The VO x @MoO3 nanorod composite is obtained by a facile electrochemical method. The effective interaction between the two components induces synergistic effects which largely enhance the electrochemical performance. The composite shows a high capacitance of 1166 mF cm −2 at the high current density of 100 mA cm −2, which doubles the sum of single electrodes.